PENINGKATAN KINERJA MANAJEMEN MELALUI MITOS DAN ISTILAH MANAJEMEN - M. TAHER RAMBE (JURNAL ILMIAH MAKSITEK, 2018)
The writing of this paper aims to determine the improvement of management performance through myths and terms of management. Writing method uses library research method. From the results of the discussion, it can be concluded that there are no definite formulations and limits on the content and characteristics of high-performing organizations and how the process is achieved. What is certain is that many recipes and concepts have been offered. But the concept-prescription is generally universalistic and oversimplifies the reality of the organization. It is time for managers not to expect the recipe and concept as a powerful tool to boost organizational performance in a revolutionary manner. Improving performance is not a static shortcut, but a relentless step that recognizes the ups and downs of successes and failures, which are highly dependent on both contextual and controlled contextual factors which require various combinations of actions and conditioning to achieve them. It's time for managers to think more reflexively, looking for the real root of the problem rather than directly adopting the answer